Water Quality of Green Roofs by Using Oil Palm Empty Fruit Bunch Fiber as A Filter Layer - Zakaria, Siti Hazirah; Mohd Arish @Arshad, Nur Aini (Progress in Engineering Application and Technology, 2024)
A green roof is a technological solution that incorporates vegetation and growing medium, which are placed on top of a filter and waterproofing membrane. Contaminants may be present in the runoff water quality originating from green roofs, either due to external factors in the surrounding environment or as a result of the green roof substrate layer. The objectives of this study are to analyze the water quality of green roofs using empty fruit bunch fiber from oil palm as a filter layer and develop the model of a green roof by using oil palm empty fruit bunch fiber as a filter layer. Oil palm empty fruit bunch fiber is appropriate for use as low materials to create roofing material despite their great number and extremely low value. The water quality parameter tests which are pH, Turbidity, Ammonia, TSS, Dissolved Oxygen, Chemical Oxygen Demand and Biochemical Oxygen Demand were conducted in the laboratory. This study involves the planting of three green roof model with three distinct types of filter layers which is sample 1 with 40mm, and sample 2 with 20mm. All the results were compared to the Water Quality Index (WQI) where the WQI results for Sample 1 is 76 (Class III), Sample 2, is 77 (Class II), and Sample 3 is 73 (Class III), It can be concluded that the water sample from Sample 2 the green roof is suitable for Fishery II (sustaining aquatic life and ecosystems) and water for recreational use, including activities such as swimming, fishing, boating, and other water-based pursuits